Rifaximin reduces the incidence of spontaneous bacterial peritonitis, variceal bleeding and all‐cause admissions in patients on the liver transplant waiting list. Issue 4 (6th June 2019) - Salehi, Shayon; Tranah, Thomas H.; Lim, Samuel; Heaton, Nigel; Heneghan, Michael; Aluvihare, Varuna; Patel, Vishal C.; Shawcross, Debbie L.
Summary: Background: Rifaximin reduces the risk of overt hepatic encephalopathy (HE) and is associated with significant reductions in hospitalisations and 30‐day readmissions. Aim: To examine the outcomes of patients listed for liver transplantation with a diagnosis of HE on rifaximin compared to those naïve to the drug. Methods: Patient records of those listed for liver transplantation over a 2‐year period were retrospectively reviewed. Patients were included if they had at least two episodes of overt HE resulting in hospitalisation or were encephalopathic at the time of assessment. Results: Of the 622 patients listed for transplantation, 101 had HE. Sixty‐six patients were treated with rifaximin and 35 were naïve at listing. The use of concurrent lactulose was not significantly different between groups. Median MELD score was similar (15 [14‐16)] rifaximin‐treated and 16 [14‐18] rifaximin‐naïve). Patients on the waiting list treated with rifaximin had reduced all‐cause admissions, episodes of spontaneous bacterial peritonitis and variceal bleeding. Mean length of stay was 9 days (95% CI 6‐12) in the rifaximin‐treated group vs 14 (95% CI 7‐21) in the rifaximin‐naïve group. Multivariate regression analysis demonstrated that rifaximin was independently associated with an increase in average days to readmission (adjusted effect estimate 71, 95% CI 3‐140 days) and reduced likelihood of requirement for prioritisation on the waiting list (odds ratio 0.29; 95% CI 0.89‐0.93). Conclusion: Rifaximin prescribed for HE in patients listed for liver transplantation improved outcomes with significant reduction in admissions related to spontaneous bacterial peritonitis, ascites and variceal bleeding.